Transthoracic Vector Flow Imaging in Pediatric Patients with Valvular Stenosis – A Proof of Concept Study - Nguyen, Tin-Quoc; Bechsgaard, Thor; Schmidt, Michael Rahbek; Juul, Klaus; Moshavegh, Ramin; Lönn, Lars; Nielsen, Michael Bachmann; Jensen, Jørgen Arendt; Hansen, Kristoffer Lindskov (Ultrasound International Open, 2021)
Purpose Continuous wave Doppler ultrasound is routinely used to detect cardiac valve stenoses. Vector flow imaging (VFI) is an angle-independent real-time ultrasound method that can quantify flow complexity. We aimed to evaluate if quantification of flow complexity could reliably assess valvular stenosis in pediatric patients.Materials and Methods Nine pediatric patients with echocardiographically confirmed valvular stenosis were included in the study. VFI and Doppler measurements were compared with transvalvular peak-to-peak pressure differences derived from invasive endovascular catheterization.Results Vector concentration correlated with the catheter measurements before intervention after exclusion of one outlier (r=−0.83, p=0.01), whereas the Doppler method did not (r=0.49, p=0.22). The change in vector concentration after intervention correlated strongly with the change in the measured catheter pressure difference (r=−0.86, p=0.003), while Doppler showed a tendency for a moderate correlation (r=0.63, p=0.07).Conclusion Transthoracic flow complexity quantification calculated from VFI data is feasible and may be useful for assessing valvular stenosis severity in pediatric patients.
Keywords: catheters; echocardiography; vector flow imaging, valvular stenosis, pressure gradient